Negative Theology Construction in Islamic Education System: An Analytical Study - Umiarso Umiarso (Edukasia Islamika, 2020)
This study focuses on the construction of the negative concept of divinity (theology) developed in the educational system such as madrasas or pesantren. Therefore, the aim of this study is to analyze the construction of negative theology in the Islamic education system developed in madrasas or pesantren in Malang, East Java, Indonesia. To critically discuss the issue, this study used a qualitative approach with phenomenological research design and Miles and Huberman’s framework in analyzing the data. Study findings expose that negative theological discourse denoted an arena for the prophetization of divine values ​​whose style of expression was apophatic. Apparently, it constructs its theological knowledge as well as “rejects” the knowledge construction with the logic of negation and paradox. The implications for the Islamic education system are the framework of educational objectives is oriented to aspects of humanity and divinity; or the profane and transcendental dimension. It indicates that negative theology contributes to novel insights into the axiology of Islamic education.